Therapeutic effect and mechanism of combination therapy with ursolic acid and insulin on diabetic nephropathy in a type I diabetic rat model - Liu, Yang; Zheng, Jin-Yan; Wei, Zhi-Tao; Liu, Shu-Kun; Sun, Ji-Lei; Mao, Yin-Hui; Xu, Yong-De; Yang, Yong (Frontiers in Pharmacology, 2022)
This work aims to investigate the therapeutic effect of ursolic acid (UA) plus insulin (In) on diabetic nephropathy (DN) in streptozotocin (STZ)-induced T1DM rats. The experimental groups and operational details are as follows: A total of thirty-two SD rats were divided into four groups: the DN model group (DN, n = 8), DN + In treatment group (DN + In, n = 8), DN + In + UA administration group (DN + In + UA, n = 8), and negative control group (control, n = 8). After 8 weeks, changes in renal function indices and pathological damage were assessed. Additionally, oxidative stress-, apoptosis-, and fibrosis-related proteins in kidney tissue were measured. Compared with the control group, the vehicle group showed higher levels of creatine, blood urea nitrogen, urinary protein, apoptosis, and lipid peroxidation; lower superoxide dismutase levels; more severe levels of pathological kidney damage and renal fibrosis; and a deepened degree of EMT and EndMT. Better outcomes were achieved with the combined treatment than with insulin-only treatment. The improvement of TGF-β1, phosphorylated p38 MAPK, FGFR1, SIRT3 and DPP-4 expression levels in renal tissues after combination therapy was greater than that after insulin-only treatment. This study shows that the combination of insulin and UA significantly improved the pathological changes in the renal tissue of T1DM rats, and the underlying mechanism may be related to improving apoptosis and oxidative stress by regulating p38 MAPK, SIRT3, DPP-4 and FGFR1 levels, thereby blocking TGF-β signaling pathway activation and inhibiting EMT and EndMT processes.